ANALISIS TIME-SERIES INSAR (INTERFEROMETRIC SYNTHETIC APERTURE RADAR) UNTUK PEMANTAUAN DEFORMASI DI PORONG, SIDOARJO TAHUN 2014 - 2018 - Alkadri, Fawaz
On May 29, 2006, there has been a burst of fluid (steam/water) and solid mud in Porong, Sidoarjo. Some researchers refer to the phenomenon in the area as "LUSI" hot mud. Experts classify this incident as "Mud Volcano or Mud Dome". Based on previous research, until now, this phenomenon is presumed to have caused land subsidence to occur. By using remote sensing satellites, it is possible to observe the deformation of the earth's surface on a wide scale at any time depending on the available data. Widely observed deformation (area-based), in recent years, has begun to be applied and developed by researchers. This observation technique is also known as InSAR (Interferometric Synthetic Aperture Radar). InSAR method is a geodetic method that utilizes SAR satellite images by interpreting two or more images so that the measurement of the deformation phase values can be carried out efficiently. The purpose of this study is to determine the deformation value in the line-of-sight direction in Porong District, Sidoarjo in 2014 - 2018 by utilizing the ALOS-2 SAR image. Observations are made by 'stacking' interferograms (stacking images) which are formed from 2-pass differential interferometry so that the deformation value can be defined in time series. The value of land subsidence that occurs at the center of the burst reaches 0.2 m/year within 5 years of observation. Meanwhile, land subsidence is proven to have a strong correlation with the volume of the LUSI burst, with a correlation coefficient of -0.9. In this observation, an observation is made on a plot that passes through the center of the burst. The results show that at the center of the burst a deformation pattern is formed which can be defined in a certain deformation model.